2005
DOI: 10.1029/2004gb002400
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and bleaching‐induced changes in coral reef metabolism and CO2 flux

Abstract: [1] Monitoring seawater CO 2 for a full year with seasonal observations of community metabolism in Ishigaki Island, Japan, revealed seasonal variation and anomalous values owing to the bleaching event in 1998. The daily average pCO 2 showed a seasonal pattern on an annual scale, 280 to 320 matm in winter and 360 to 400 matm in summer, which was determined primarily by the seasonal change in seawater temperature. By contrast, the range in the diel variation in pCO 2 , 400 to 500 matm in summer 200 to 300 matm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 44 publications
(60 reference statements)
9
102
0
Order By: Relevance
“…The quantitative relationships between reef carbonate chemistry, reef scale biogeochemistry, hydrodynamics, local reef geomorphology, and ecological community composition have been examined in detail in a new and useful model . Comparing these values to pre-1998 El Nino bleaching event estimates from 1994, NCP, respiration, gross production, and calcification dropped by 32%, 46%, 44%, and 57%, respectively, by 2000 (Kayanne et al 2005). The NCC and NCP rates we report here, 220.4 (6 7.8) to 41.2 (6 37.7) mmol C m 22 h 21 and 77.3 (6 95) to 64 (6 22) mmol C m 22 h 21 , respectively, for a back-reef environment are an order of magnitude greater than those reported for the large western lagoon and the reef flat habitat on Palau.…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative relationships between reef carbonate chemistry, reef scale biogeochemistry, hydrodynamics, local reef geomorphology, and ecological community composition have been examined in detail in a new and useful model . Comparing these values to pre-1998 El Nino bleaching event estimates from 1994, NCP, respiration, gross production, and calcification dropped by 32%, 46%, 44%, and 57%, respectively, by 2000 (Kayanne et al 2005). The NCC and NCP rates we report here, 220.4 (6 7.8) to 41.2 (6 37.7) mmol C m 22 h 21 and 77.3 (6 95) to 64 (6 22) mmol C m 22 h 21 , respectively, for a back-reef environment are an order of magnitude greater than those reported for the large western lagoon and the reef flat habitat on Palau.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we still know little in regards to how the photosynthesis:respiration ratio is regulated in reef systems on seasonal and large spatial scales. Photosynthesis and respiration quantified by O 2 evolution of a coral community (Kayanne et al 2005) as well as for individual coral species (Al-Sofyani & Davies 1992, Nakamura et al 2004) have previously been documented over seasonal scales. However, the findings in these studies were not consistent, suggesting that local environmental conditions, and possibly adaptive traits of the investigated holobionts, can exert important influences on metabolic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, 5.8 kg CaCO 3 /m 2 /y will be required to maintain wave height reduction by the facies under 0.98 m SLR by 2100 (highest value for RCP 8.5). Field measurements of the reef crest community at the core site following the mass bleaching event in 1998 showed that the calcification rate decreased from 130 to 74 mmol C/m 2 /day, equivalent to a rate of 4.7-2.7 kg CaCO 3 /m 2 /y (Kayanne et al, 2005). Coinciding 10 with the bleaching event, the coral cover decreased from 8.1% to 1.4% (Kayanne et al, 2005).…”
Section: Coastal Risk Reduction Through Future Reef Growthmentioning
confidence: 99%
“…Field measurements of the reef crest community at the core site following the mass bleaching event in 1998 showed that the calcification rate decreased from 130 to 74 mmol C/m 2 /day, equivalent to a rate of 4.7-2.7 kg CaCO 3 /m 2 /y (Kayanne et al, 2005). Coinciding 10 with the bleaching event, the coral cover decreased from 8.1% to 1.4% (Kayanne et al, 2005). Therefore, we assume that if the coral cover is ~1% in 2100 the corals will keep pace with 0.44 m SLR under RCP 2.6, but >8% coral cover will be needed under RCP 8.5 to reduce wave height and the risk of coastal damage at the study site.…”
Section: Coastal Risk Reduction Through Future Reef Growthmentioning
confidence: 99%